TINGKAT PENGETAHUAN PERAWAT DENGAN KEPATUHAN PELAKSANAAN HAND HYGIENE DI RUANGAN INTERNA RSUD TOTO KABILA - Sabirin B. Syukur; Euis H. Hidayat; Nadia M Laukom (Universitas Muhammadiyah Gorontalo, 2020)
Hand hygiene is activities to clean hands with alcohol-based soap and water (hand wash) or (hand rub), washing hands also acts as a breaker of disease transmission chain. Nurse hand hygiene behaviour can affect the health of nurses and clients in preventing the transmission of HAIs (Health care associated infection) infection. The objective of research was to determine correlation of nurse knowledge level with the compliance implementation of hand hygiene. The design used quantitative analytic with cross sectional method. The samples were 34 respondents used total sampling technique. The variables researched include the dependent variable is compliance with the implementation of hand hygiene and the independent variable is nurses' knowledge. The method of collecting data used questionnaire with the observation and analysis used chi square test with significance value α=0,05. The result showed there are significance correlations with P value=0,003 which means small than α value=0,05. Concluded there is correlation of nurse knowledge level with the compliance implementation of hand hygiene in interna room of RSUD Toto Kabila.